ANIMAL MODELS AND MECHANISM OF ACTION OF POLYCYSTIC OVARIAN SYNDROME: A REVIEW - Diksha Sharma; Bhumi Ruhil
Ensuring the well-being of reproductive system is crucial for overall bodily health. Currently, polycystic ovarian syndrome (PCOS) has emerged as a significant health concern among women in their reproductive age. It is an endocrine disorder characterized by irregular menstrual cycle, hyperandrogenism, hirsutism and anovulation in women. In - depth exploration of the literature was conducted through comprehensive searches across various online databases, texts, websites and theses. This review aims to provide information about the dose/route, structure and mechanism of various agents. We elaborate several rodent models of hormonal, environmental, lifestyle induced PCOS, non-mammalian models as well as genetic models and give recommendations on PCOS model selection. Nonetheless, further studies are needed to propose the drug therapy and mechanistic approaches required for the treatment of PCOS.